Adrenal Dysfunction Caused by a Critical Condition During Extracorporeal Membrane Oxygenation - N. E. Altshuler; K. K. Gubarev; M. B. Kutsy; K. A. Popugayev (Неотложная медицинская помощь, 2023)
ABSTRACT Currently, the assessment of adrenal dysfunction in critically ill patients and ways to correct adrenal dysfunction with hormone replacement therapy are extremely difficult. The results of the Cochrane meta-analysis “Corticosteroids for treating sepsis” showed that survival was higher among patients with respiratory distress syndrome and septic shock who received glucocorticoids (mainly hydrocortisone) for a long course and at low doses. These results are in very good agreement with the concept of critical illness-related corticosteroid insufficiency (CIRCI) development in the subacute and chronic stages of a critical condition and the need to prescribe glucocorticoid replacement therapy in this situation. International guidelines for the treatment of sepsis and septic shock for 2016 suggest avoiding the use of hydrocortisone in patients who developed sepsis. Only the development of septic shock, and the persisting instability of hemodynamics against the background of achieving normovolemia and high doses of vasopressors, are the indication for the use of hydrocortisone 200 mg intravenously. In 2021, revised guidelines approved the administration of hydrocortisone to patients in septic shock without waiting for an adequate fluid loading to be achieved. In contrast to these recommendations, the Society of Critical Care Medicine and the European Society of Intensive Care Medicine, in their recommendations for 2017, suggest for adrenal dysfunction caused by a critical condition in patients with severe community-acquired pneumonia and circulatory arrest the use of hydrocortisone in the early stages, before the development of multiple organ failure. The existing guidelines do not consider the use of hydrocortisone in critical conditions during extracorporeal membrane oxygenation (ECMO). The timing of hydrocortisone administration to critically ill patients requiring ECMO, and the duration of this therapy are currently a topical issue for intensive care specialists. To ensure the completeness of the list of references for compiling a systematic review in the databases MEDLINE, PubMed, MeSH, eLibrary.EN a search was performed for matches, by keywords, and phrases, the roots of keywords, taking into account possible word forms, by the first two hundred relevant links, in case there were so many links. The exclusion criterion was “the use of synthetic glucocorticoids”.